Współczesnej publicystyki prasowej oblicza różne - Wojtak, Maria (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
The analyses presented in the article suggest that contemporary column writing can be divided into the basic mainstream and modernizing sub-currents. The mainstream is flexibly inscribed into the tradition of press publishing, and characterized by recentness of problems discussed (although historical ones are not avoided), importance of themes, defense of values accepted as primary in our cultural area, and convincing persuasion, based on argument and logical support for opinions, reference to authority, inative and suggestive quality. Modernizing sub-currents, on the other hand, should be perceived as experimental activity, authored subjectively, polyphonic, exposing and satirical, provocative and appealing to readers in the consctruction of a common world view, based on common interests, and community of ethical principles, language, and laughter (interestingly, these parameters do not have to co-occur). The phenomenon of mixing all currents in a text seems to be the most typical quality of contemporary column writing. The functioning of media content with a given dominant introduces a modernizing stir into this order. The article presents a more careful analysis of several examples of these tendencies.